Treatment of model solutions and wastewater containing selected hazardous metal ions using a chitin/lignin hybrid material as an effective sorbent. (15th December 2017) - Bartczak, Przemysław; Klapiszewski, Łukasz; Wysokowski, Marcin; Majchrzak, Izabela; Czernicka, Weronika; Piasecki, Adam; Ehrlich, Hermann; Jesionowski, Teofil
Abstract: A chitin/lignin material with defined physicochemical and morphological properties was used as an effective adsorbent of environmentally toxic metals from model systems. Particularly significant is its use in the neutralization of real industrial wastes. The ions Ni 2+, Cu 2+, Zn 2+ and Pb 2+ were adsorbed on the functional sorbent, confirming the high sorption capacity of the newly obtained product, primarily due to the presence on its surface of numerous active functional groups from the component biopolymers. The kinetics of the process of ion adsorption from model solution were investigated, and the experimental data were found to fit significantly better to a type 1 pseudo-second-order kinetic model, as confirmed by the high correlation coefficient of 0.999 for adsorption of both nickel(II) copper(II) zinc(II) and lead(II) ions. The experimental data obtained on the basis of adsorption isotherms corresponded to the Langmuir model. The sorption capacity of the chitin/lignin material was measured at 70.41 mg(Ni 2+ )/g, 75.70 mg(Cu 2+ )/g, 82.41 mg(Zn 2+ )/g and 91.74 mg(Pb 2+ )/g. Analysis of thermodynamic parameters confirmed the endothermic nature of the process. It was also shown that nitric acid is a very effective desorbing (regenerating) agent, enabling the chitin/lignin material to be reused as an effective sorbent of metal ions. The sorption abilities of the chitin/lignin system with respect to particular metal ions can be ordered in the sequence Ni 2+ <Cu 2+ <Zn 2+ <Pb 2+ . Tests were also performed with the adsorption of ions of nickel(II), copper(II), zinc(II) and lead(II) from wastewater obtained from galvanization and battery production plants, confirming the ability of the chitin/lignin sorbent to adsorb harmful ions from real industrial wastes. Graphical abstract: Highlights: Chitin/lignin hybrid material with enhanced sorption properties is proposed. Type 1 of pseudo-second-order model describes the kinetics of the ions adsorption. The experimental data of adsorption isotherms correspond to the Langmuir model. Thermodynamic parameters confirmed the endothermic nature of the process. The sorption ability of the chitin/lignin material is the best for Pb(II) removal.